The Power of a Pledge Agreement Made Under Circumstances of Force - Noor, Aslan; Nurdiani, Herlin; Sari, Raisa; Azzahra, Tasya Dania (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
To borrow or lend money is one example of an economic and financial transaction that often involves a contractual agreement. Collateral is an object that the debtor (borrower) gives to the creditor (lender) in exchange for a loan. "Pawned" describes the thing that serves as collateral. A creditor may sell a pawned item to recover a debt in the event that the debtor does not make their loan repayment as agreed upon. Consensus agreements reached under pressure tend to be unjust and hurtful to one side. The concepts of fairness and equilibrium in contracts are violated by this. Consequently, we must investigate the means by which agreements entered into under duress may be rescinded or rectified, as well as the laws that govern the protection of parties in such situations.